Textile effluents and dye contamination: assessment of ecotoxicological risks and weaknesses in industrial management - Moura, Luiz Eduardo Freitas de; Soares, Francisco Igo Leite; Dantas, Emyllene (Brazilian Journal of Production Engineering, 2026)
The textile industry stands out as a dynamic sector of the economy, driven by the constant search for dyes that increase dyeing efficiency and reduce the consumption of natural resources, especially water and raw materials. The improper disposal of the waste produced causes environmental problems, such as changes in water coloration, the degradation of water quality, and the compromise of aquatic life. Given this issue, this study consists of a literature review aimed at gathering data using the following databases: Google Scholar, Elsevier, ScienceDirect, Springer, and Nature. After the data collection, the articles were organized into two thematic axes, environmental problems and risks to human health, and analyzed individually and in groups to obtain the findings. Based on these implications, it was observed that the waste has a high contamination potential and represents a risk that extends from the ecosystem to human beings. Therefore, it was concluded that there is an urgent need to modernize the treatment of this waste, alongside the immediate strengthening of inspections and the strict enforcement of environmental regulations through effective public policies. In this way, the importance of integrating environmental responsibility and industrial development as pillars of a balanced production model is reinforced.
Keywords: Dyes; Textile industry; Public policies